The Effect of Self Service Technology and Perceived Enjoyment on Interest in Reusing Self-Ordering Kiosk on Gen-Z in Medan City - Jeremi Siagian; Hafiza Adlina (Journal Business Administration: Entrepreneurship and Creative Industry, 2024)
Technological developments in the food and beverage industry sector triggered by the Covid-19 pandemic have been presented by McDonalds to maintain distance by utilizing the role of self-service technology that prevents direct contact with employees and utilizes the performance of the self-ordering kiosk. Perceived enjoyment is also needed to increase GenZ's desire to have an interest in reusing the self-ordering kiosk at McDonald's. This study aims to determine the effect of self-service technology and perceived enjoyment on interest in reusing the self-ordering kiosk at Gen-Z McDonald's in Medan City. The method used is quantitative by involving 100 Gen-Z people as samples. The results of this study indicate that self-service technology and perceived enjoyment have a significant effect on the interest in reusing the self-ordering kiosk at Gen-Z McDonald's in Medan City by 81.9%. This means that the role of self-service technology and perceived enjoyment felt by Gen-Z is very well realized, although it is still necessary to improve the performance of the self-ordering kiosk in order to have an interest in reusing the self-ordering kiosk.